Does the increase in health insurance benefits have different effects on the health of middle-aged and older people individuals in rural areas? Analysis based on quantile difference-in-differences method - Qin, Cheng; Wang, Xueyi (Frontiers in Public Health, 2024)
In the context of healthy aging, enhancing health performance is an intrinsic requirement for the development and reform of the health insurance system. This paper mainly discusses the health effects of increasing medical insurance benefits on people with different levels of health. So this paper utilizes multiple rounds of data from the China Health and Retirement Longitudinal Study (CHARLS) and employs the quantile difference-in-differences method to systematically investigate the impact effects of the integration of urban and rural residents' health insurance on the frailty levels of rural middle-aged and older people individuals. The research findings are as follows: Firstly, the integration of urban and rural resident health insurance has mitigated the frailty level of rural older people individuals, with a more pronounced impact on those with poorer health statuses. Secondly, in terms of heterogeneity analysis, the health performance effects of the urban-rural health insurance integration policy are more significant among the older people population and in the western regions. Thirdly, the integration of urban and rural resident health insurance primarily improves health by reducing the burden of medical expenses, with a greater impact on the older people population with poorer health statuses. Based on the research findings, we recommend addressing the disparities in healthcare benefits across various insurance systems, alleviating the financial burden of healthcare for impoverished individuals, and consistently improving the coordination of healthcare insurance policies for both urban and rural residents.